MERS coronavirus neutralizing antibodies in camels, eastern Africa, 1983-1997 - Muller, M.A.; Corman, V.M.; Jores, Joerg; Meyer, B.; Younan, M.; Liljander, Anne M.; Bosch, B.J.; Lattwein, E.; Hilali, Mosaad; Musa, B.E.; Bornstein, S.; Drosten, C. (Centers for Disease Control and Prevention, 2014)
To analyze the distribution of Middle East respiratory syndrome coronavirus (MERS-CoV)–seropositive dromedary camels in eastern Africa, we tested 189 archived serum samples accumulated during the past 30 years. We identified MERS-CoV neutralizing antibodies in 81.0% of samples from the main camel-exporting countries, Sudan and Somalia, suggesting long-term virus circulation in these animals.